THYROTOXIC CARDIOMYOPATHY COMPLICATED BY FULMINANT HEPATIC FAILURE: A CASE REPORT - Gayathiri, Narendranath; Theviyaah, Thiagarajan; Jolyn, Susinadan; Elliyyin, Katiman; Hazwani, Aziz (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Thyrotoxic cardiomyopathy with cardiac failure can lead to liver congestion and ischaemic hepatitis. Fulminant hepatic failure secondary to thyrotoxic cardiomyopathy is rare. CASE We report a 45-year-old woman with strong family history of hyperthyroidism. She presented with palpitations and cardiac failure symptoms for a month. Electrocardiograph showed atrial fibrillation. Echocardiogram revealed a preserved ejection fraction (55%), mid-septal wall hypokinesia, severe mitral and tricuspid regurgitation, with pulmonary hypertension. She had an elevated free T4 (fT4) level of 16.4 pmol/L (7.86-14.41 pmol/L) and free T3 (fT3) level of 7.6 pmol/L (3.10-6.80 pmol/L). TSH receptor antibody was elevated 13.7 IU/L (<1.75 IU/L) consistent with Graves’ Disease. She was treated for thyroid storm and initiated on an anticoagulant. She was discharged with carbimazole 30 mg OD and bisoprolol 2.5 mg OD. After 10 days, she returned with worsening cardiac failure, high-grade fever and jaundice. Upon admission, the fT4 level was 12 pmol/L. Her liver transaminases were normal except for hyperbilirubinemia secondary to liver congestion. Subsequently, transaminases showed rapid progression of liver failure with peak aspartate aminotransferase (AST) of more than 10,000 U/L, total bilirubin of 481.3 umol/L (5.0-21.0 umol/L), and severe coagulopathy. She required mechanical ventilation due to hepatic encephalopathy. Ultrasonography of the hepatobiliary system showed cholelithiasis with acute cholecystitis. Budd-Chiari Syndrome was ruled out since the hepatic veins were patent. Viral hepatitis was likewise ruled out. She was managed with N-acetylcysteine, diuretics, and second-line anti-thyroid treatment (cholestyramine, hydrocortisone, and Lugol’s solution). Her sepsis responded to intravenous meropenem. She was not suitable for liver transplantation due to multi-organ failure after consulting the hepatology team. CONCLUSION A comprehensive approach involving cardiac evaluation with echocardiogram, assessment of liver dysfunction, and consideration of autoimmune causes of liver failure is crucial in the management of patients with thyrotoxicosis and liver failure. Liver transplant is an option in the management of thyrotoxicosis with fulminant liver failure.